Propagation and Wireless Channel Modeling Development on Wide-Sense Vehicle-to-X Communications - Wenyi Jiang; Ke Guan; Zhangdui Zhong; Bo Ai; Ruisi He; Binghao Chen; Yuanxuan Li; Jia You (International Journal of Antennas and Propagation)
The need for improving the safety and the efficiency of transportation systems has become of extreme importance. In this regard, the concept of vehicle-to-X (V2X) communication has been introduced with the purpose of providing wireless communication technology in vehicular networks. Not like the traditional views, the wide-sense V2X (WSV2X) communications in this paper are defined by including not only vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communications but also train-to-X (T2X) communications constituted of train-to-train (T2T) and train-to-infrastructure (T2I) communications. All the information related to the wide-sense V2X channels, such as the standardization, scenarios, characters, and modeling philosophies, is organized and summarized to form the comprehensive understanding of the development of the WSV2X channels.